Acute polyarticular synovitis as a rare presentation of Kaposi sarcoma - Larissa Larsen; Mondhipa Ratnarathorn; Nasim Fazel (Wolters Kluwer Medknow Publications, 2014)
Patients with HIV are prone to a number of unusual infectious and malignant conditions, typically resulting from declining immune function. However, there are also a few of reports of HIV associated conditions potentially created by viral release of interleukin-6 (IL-6). Herein, we present a case of HIV IL-6-related systemic inflammatory syndrome, a Kaposi sarcoma (KS)-associated syndrome in the absence of multicentric Castleman disease (MCD).